High concentration of the plasma microparticles for venous thromboembolism associated with lung cancer. (19th February 2020) - Wang, Meiru; Huang, Xiaoxi; Zhu, Min; Zhang, Shu; Zhang, Yuhui
Abstract: Background: Limited biomarkers are used for predicting risk of venous thromboembolism (VTE) associated with cancer. Circulating microparticles (MPs), especially tissue factor‐ positive microparticles (TF + MPs), play an important role in the development of cancer‐associated VTE. This study investigated the predictive value of plasma MPs and TF + MPs for VTE in lung cancer. Methods: A case‐control study was performed using the Beijing Chao‐Yang Hospital Lung Cancer Registry. Cases had VTE occurring 3 months before or after a diagnosis of lung cancer. Controls were patients with lung cancer without VTE matched for age, histology and stage. The proportion of MPs and TF + MPs was evaluated by light‐scatter‐based flow cytometry. Results: Between January 2012 and December 2015, 30 cases with VTE and 60 controls without VTE were included. The proportion of MPs and TF + MPs was significantly more elevated in patients with VTE than in those without VTE ( P  < 0.05 for both). By multivariate logistic regression analysis, MPs (OR 1.153; 95% CI 1.068‐1.245; P  < 0.001) and adenocarcinoma (OR 3.223; 95% CI 1.062‐9.782; P  = 0.039) were significantly associated with VTE. The sensitivity of the proportion of MPs in diagnosing VTE was 93.3%, and the specificity was 70.0%. The sensitivity of the proportion of TF + MPs in diagnosing VTE was 66.7%, and the specificity was 88.3%. The area under the receiver operating characteristic curves for the diagnostic of the proportion of MPs and TF + MPs values were 0.836 (95% CI 0.750‐0.922, P  < 0.001) and 0.828 (95% CI 0.736‐0.920, P  < 0.001) respectively. Conclusion: The elevated proportion of MPs and TF + MPs might help predict VTE associated with lung cancer.